What It Takes to Be a Pioneer: Ability Expectations From Brain-Computer Interface Users. - Kögel, Johannes; Wolbring, Gregor (NanoEthics, 2020)
Brain-computer interfaces (BCIs) are envisioned to enable new abilities of action. This potential can be fruitful in particular when it comes to restoring lost motion or communication abilities or to implementing new possibilities of action. However, BCIs do not come without presuppositions. Applying the concept of ability expectations to BCIs, a wide range of requirements on the side of the users becomes apparent. We examined these ability expectations by taking the example of therapeutic BCI users who got enrolled into BCI research studies due to particular physical conditions. Some of the expectations identified are quite explicit, like particular physical conditions and BCI "literacy". Other expectations are more implicit, such as motivation, a high level of concentration, pain tolerance, emotion control and resources. These expectations may produce a conception of the human and a self-understanding among BCI users that objectify the body in favour of a brain-centred, cerebral notion of the subject which also plays its part in upholding a normality regime.